A BIBLIOMETRIC ANALYSIS OF TRENDS IN ISLAMIC THEOLOGY RESEARCH: MAPPING THE LANDSCAPE OF SCHOLARLY CONTRIBUTIONS - HARNEDI, JONI; NASUTION, AWAL KURNIA PUTRA; MUNANDAR, IMAM; QODIR, IBNU; HARAHAP , AHMAD YUNUS MOKOGINTA (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
This study provides a comprehensive overview of research developments in the field of Islamic theology over the past two decades. Utilizing data from Scopus-indexed databases, the research conducts a bibliometric analysis to identify publication trends, international author collaborations, and emerging thematic areas within the discipline. The findings reveal a steady increase in scholarly output and a diversification of research topics, reflecting the growing relevance of Islamic theology in addressing contemporary global challenges. A notable trend is the rise in cross-national academic cooperation, indicating the increasing globalization of Islamic theological discourse. This study not only maps key contributors and institutions but also uncovers interdisciplinary linkages, particularly with fields such as ethics, environmental studies, and social sciences. By highlighting understudied areas and gaps in the literature, the analysis offers valuable insights for future research directions. Overall, the study captures the dynamic evolution of Islamic theology and its expanding role in global academic inquiry.